2013
DOI: 10.1016/j.jad.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cognitive versus somatic symptoms of depression and event-free survival following acute myocardial infarction in the Enhancing Recovery In Coronary Heart Disease (ENRICHD) study

Abstract: Background Randomized controlled trials focusing on the effects of antidepressant treatment in cardiac patients have found modest effects on depressive symptoms but not on cardiac outcomes. A secondary analysis was conducted on data from the Enhancing Recovery in Coronary Heart Disease trial to assess whether changes in somatic or cognitive depressive symptoms following acute MI predicted event-free survival and whether the results differed per treatment arm (cognitive behavior therapy or care as usual). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…In patients with stable coronary heart disease, somatic symptoms of depression are associated with cardiac events, while there is no significant association of cognitive symptoms of depression with cardiac prognosis (Hoen et al, 2010). Later the same results were found for somatic symptoms of depression in patients that suffered acute myocardial infarction (Roest et al, 2013). Additionally, in chronic heart failure somatic symptoms of depression are associated with all-cause mortality, while cognitive symptoms of depression are not (Schiffer et al, 2009).…”
Section: The Influence Of Depression On Prognosis In Patients With Cvdmentioning
confidence: 67%
“…In patients with stable coronary heart disease, somatic symptoms of depression are associated with cardiac events, while there is no significant association of cognitive symptoms of depression with cardiac prognosis (Hoen et al, 2010). Later the same results were found for somatic symptoms of depression in patients that suffered acute myocardial infarction (Roest et al, 2013). Additionally, in chronic heart failure somatic symptoms of depression are associated with all-cause mortality, while cognitive symptoms of depression are not (Schiffer et al, 2009).…”
Section: The Influence Of Depression On Prognosis In Patients With Cvdmentioning
confidence: 67%
“…21 Indeed, these symptom clusters have been shown to have differential impact on HF outcomes 22, 23 as well as other indices of cardiovascular function. 2429 For example, some studies found that the somatic symptoms cluster (e.g., sleep disturbance, appetite changes, and low energy) was the strongest predictor across a variety of outcomes, 22, 25, 29 whereas other studies reported similar results for the nonsomatic symptom clusters (e.g., cognitive, affective, or behavioral symptoms). 23, 2628 For example, Schiffer et al 22 found that individuals with high somatic symptom scores had a greater incidence of mortality than those with low scores (31% vs. 15%; hazard ratio = 2.3).…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressant medications, such as sertraline, have been reported to result in decreased mortality and MI risks for patients with coronary artery disease and concomitant depression [30,31]. Changes in depressive symptoms were also found to be related to improved outcomes in patients with MI [32]. The effect of antidepressant medications on patients undergoing PCI should be verified in future studies.…”
Section: Discussionmentioning
confidence: 97%